Application of the Weight Product Method on a Decision Support System for the Latest Mobile Recommendations - Rima Tamara Aldisa; Mohammad Aldinugroho Abdullah (IJISTECH (International Journal of Information System and Technology), 2022)
Mobile phones or what can be called mobile phones are tools for electronic communication that can be used wherever and whenever you are and can send and receive messages. To understand this, a recommendation system is needed to assist mobile phone buyers in choosing, finding, and finding phones that match what the user wants and according to the specifications desired by the user. The author makes the Application of the Weight Product Method in the Latest Mobile Recommendation Decision Support System. Here the author uses two methods, namely the waterfall method for the initial system development process, the second is the Weight Product method to find alternative values or the best results using several calculation formulas and get the best results 0.4183